NITROGEN CYCLING IN INDONESIAN AGRICULTURE AROUND 1968 TO 2008 AND ITS ENVIRONMENTAL IMPACTS - Tajuddin BANTACUT (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
The objectives of this study were to examine the efficiency of nitrogen and its lost to the environment, to estimate its environmental impacts and their mitigation measures. Nitrogen mass-balance models were developed to determine production, efficiency and the nitrogen losses. The results showed the trend of the system, increased the lost and decreased the efficiency of nitrogen fertliser around 1968 dan 2008.  The material balance model outputs predicted that around 140 kg N/ha.year in 2008 were lost and entering the environment or ecosystem. The future of Indonesian agriculture will be more intensive and fertiliser application will increase. Fertiliser impacts are decreased of nitrogen efficiency, soil organic matters, macro-elements and organisms, and groundwater contamination and air pollution. It is strongly recommended that the future of Indonesian agricultural development should sustain the production by optimising the input and cut the losses.